Comparison of Moringa Oleifera Seeds Oil Characterization Produced Chemically and Mechanically - Ali, Eman N.; K. N. S., Muhamad (IOP Publishing Ltd, 2016)
It is established that virtually every part of the Moringa oleifera tree (leaves, stem, bark, root, flowers, seeds, and seeds oil) are beneficial in some way with great benefits to human being. The tree is rich in proteins, vitamins, minerals. All Moringa oleifera food products have a very high nutritional value. They are eaten directly as food, as supplements, and as seasonings as well as fodder for animals. The purpose of this research is to investigate the effect of seeds particle size on oil extraction using chemical method (solvent extraction). Also, to compare Moringa oleifera seeds oil properties which are produced chemically (solvent extraction) and mechanically (mechanical press). The Moringa oleifera seeds were grinded, sieved, and the oil was extracted using soxhlet extraction technique with n-Hexane using three different size of sample (2mm, 1mm, and 500μm). The average oil yield was 36.1%, 40.80%, and 41.5% for 2mm, 1mm, and 500μm particle size, respectively. The properties of Moringa oleifera seeds oil were: density of 873 kg/m3, and 880 kg/m3, kinematic viscosity of 42.2mm2/s and 9.12mm2/s for the mechanical and chemical method, respectively. pH, cloud point and pour point were same for oil produced with both methods which is 6, 18°C and 12°C, respectively. For the fatty acids, the oleic acid is present with high percentage of 75.39%, and 73.60% from chemical and mechanical method, respectively. Other fatty acids are present as well in both samples which are (Gadoleic acid, Behenic acid, Palmitic acid) which are with lower percentage of 2.54%, 5.83%, and 5.73%, respectively in chemical method oil, while they present as 2.40%, 6.73%, and 6.04%, respectively in mechanical method oil. In conclusion, the results showed that both methods can produce oil with high quality. Moringa oleifera seeds oil appear to be an acceptable good source for oil rich in oleic acid which is equal to olive oil quality, that can be consumed in Malaysia where the olive oil is imported with high prices. In the same time cultivation of Moringa oleifera tree is considered to be a new source of income for the country and give more job opportunities.